History Learning through Online Learning During COVID-19 Pandemic: Teachers and Students Respond - Jamiludin, Jamiludin; Darnawati, Darnawati (FKIP Universitas Lampung, 2021)
History Learning through Online Learning During Covid-19 Pandemic: Teachers and Students Respond. Objectives: this study aims to know history learning during the COVID 19 Pandemic, know the teachers and students respond, and see the e-learning applications that are most often used and how do students respond to use the application. Method: this research used a mixed-method approach. Result: this study showed that history learning experienced differences, and there were also similarities in understanding. The difference was that initially, the teacher used face-to-face learning methods, then online learning changes that rely on internet-based applications. Not having facilities such as smartphones, laptops, and internet networks that did not support learning, made some students unactive. 55.6% of history teachers chose Google Classroom, and 44.4% selected WhatsApp as an e-learning application in teaching. Conclusion: history teachers and students faced some challenges through online learning but they still can conduct the teaching and learning process.Keywords: History Learning, Online Learning, COVID-19, E-learning Applications DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202102